Kontribusi Gaya Kepemimpinan Kepala Sekolah Berbasis Catur Naya Sandhi terhadap Kinerja Guru - Sedana, I Made; Pramana, Komang Agus Budhi Arya; Ardiawan, I Ketut Ngurah; Wiradnyana, I Gede Arya (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2020)
This study aims to explain: (1) the contribution of the headmaster's leadership style based on Catur Naya Sandhi which consists of sama bedha, dana and danda together to the variability level of teacher performance at SMA Negeri 2 Singaraja, (2) the contribution of sama aspect towards the variability level of teacher performance at SMA Negeri 2 Singaraja, (3) the contribution of bedha aspect towards the variability level of teacher performance at SMA Negeri 2 Singaraja, (4) the contribution of dana aspect towards the variability level of teacher performance at SMA Negeri 2 Singaraja and (5) the contribution of danda aspect towards the variability level of teacher performance at SMA Negeri 2 Singaraja. This research as a whole unit uses a quantitative research paradigm. The population and sample in this study were all teachers of SMA Negeri 2 Singaraja as many as 54 people. The applied method was using descriptive research and correlation studies. The results of this study found that (1) there is a contribution to the leadership style of the headmaster based on Catur Naya Sandhi which consists of sama, bedha, dana and danda together and is significant to the performance of teachers at SMA Negeri 2 Singaraja, (2) there is a contribution in the sama aspect which is significant for teacher performance by controlling the aspects of bedha, dana and danda, (3) there is a significant contribution of the bedha aspect to teacher performance by controlling the aspects of sama, dana and danda, (4) there is a contribution from the aspect of dana which shows a significant contribution to teacher performance by controlling the aspects of sama, bedha and danda and (5) there is a significant contribution of dandaÂ aspects to teacher performance by controlling the aspects of sama, bedha and dana.